Bridging Who They Are with Who They Thought They'd Be: The Effects of Gen Zers' Subjective Well-Being on Their Boycott Responses to Online and Offline Unethical Situations. Issue 2 (May 2023) - Tuan, Annamaria; Visentin, Marco; Di Domenico, Giandomenico
This research investigates the role of subjective well-being in Gen Zers' response to unethical situations that are encountered online versus offline. It empirically supports a model that incorporates moral reasoning effects and the aftermath of learning about the situation in either a first-person or third-person perspective. The findings suggest that Gen Zers are eager to show their values and participate in boycotts when facing an unethical situation. Subjective well-being plays an important role in activating versus inhibiting boycott behaviors as a response to unethical situations encountered both online and offline. Counterintuitively, Gen Zers are less likely to show support for a boycott when scoring high on well-being, since they are not willing to signal their commitment to gain social legitimacy. In fact, when coping with unethical situations, they are eager to display their true values and to enact the boycott rather than merely show support for it.